Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Can you help me compute the summation below? $$1+\frac{1}{2}+\cdots+\frac{1}{2013}+\frac{1}{1\cdot2}+\frac{1}{1\cdot3}+\cdots+\frac{1}{2012\cdot 2013}+\cdots+\frac{1}{1\cdot2\cdots2013}$$

share|improve this question
7  
I'm really not clear about what is the general term here. –  Asaf Karagila Mar 18 '13 at 21:24
1  
Just to clarify (because the $\frac{1}{1\cdot 3}$ term is perhaps wrong), we're adding up the sums of the inverse of the product of $n$ sequential elements for all $1\leq n \leq 2013$? –  Ian Coley Mar 18 '13 at 21:25
1  
So far (i.e., before corrections), this looks like a nightmare-exercise... –  DonAntonio Mar 18 '13 at 21:26
    
I have seen this question somewhere on M.SE –  Santosh Linkha Mar 18 '13 at 21:31
2  
If having $\{1,2,3\}$ then $S=1+\frac{1}{2}+\frac{1}{3}+\frac{1}{1\cdot2}+\frac{1}{1\cdot3}+\frac{1}{2\cdot‌​3}+\frac{1}{1\cdot2\cdot3}$ –  Saul of Tarsus Mar 18 '13 at 21:34

3 Answers 3

Hint:

Consider the polynomial $f(x)=\left(x+1\right)\left(x+\dfrac12\right)\ldots\left(x+\dfrac{1}{2013}\right)$.
The sum you are looking for is $f(1)-1$.

share|improve this answer
    
+1 really nice one –  Dominic Michaelis Mar 18 '13 at 21:49

Here's how it works for $n=3$.

Find a common denominator:

$$\begin{align} 1 + S &= 1 + \frac{1}{1} + \frac{1}{2} + \frac{1}{3} + \frac{1}{1\cdot2} + \frac{1}{1\cdot3} + \frac{1}{2\cdot3} + \frac{1}{1\cdot2\cdot3}\\ &=\frac{1\cdot2\cdot3 + 2\cdot3 + 1\cdot3 + 1\cdot2 + 3 + 2 + 1 + 1}{1\cdot2\cdot3}\\ &= \frac{(1+1)(1+2)(1+3)}{1\cdot2\cdot3}\\ &= \frac{2\cdot3\cdot4}{1\cdot2\cdot3}\\ &= 4 \end{align}$$ So, $S = 3$.

Generally, $(1 + S)n! = (x + 1)(x + 2) \cdots (x + n)\big|_{x=1} = (n + 1)!$, which gives $S = n$.

share|improve this answer

Let denote by $$P=(x-2013)(x-2012)\cdots(x-1)=x^{2013}+a_{2012}x^{2012}+\cdots+a_0$$ then we know the relation between the coefficients $a_i$ and the roots: $$\sigma_k=(-1)^ka_{2013-k}.$$ Now it's easy to see that the given sum is equal to $$\frac{\sigma_{2012}+\cdots+\sigma_1+1}{\sigma_{2013}}.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.